Analysis of Radial Head Implant Length with Use of Contralateral Elbow Radiographs - Athwal, George S. (JBJS Essent Surg Tech, 2012)
INTRODUCTION: This article describes a technique in which measurements are obtained from radiographs of the contralateral, normal elbow to predict the magnitude of overlengthening resulting from use of a metallic radial head prosthesis. [Figure: see text] STEP 1: OBTAIN BILATERAL ELBOW RADIOGRAPHS: Obtain bilateral digital anteroposterior radiographs of the elbows that are orthogonal to the forearm in 45° of flexion and neutral forearm rotation. STEP 2: PERFORM RADIOGRAPHIC MEASUREMENTS OF THE CONTRALATERAL, NORMAL ELBOW: Draw the angle on the radiograph of the normal elbow. [Figure: see text] [Figure: see text] [Figure: see text] [Figure: see text] STEP 3: PERFORM RADIOGRAPHIC MEASUREMENTS OF THE RADIAL HEAD IMPLANT: Draw the same lines and angle and perform the same measurements on the implant radiograph. STEP 4: CALCULATE RADIAL HEAD IMPLANT LENGTH: The virtual length of the native radial head implant (L-NRH) is subtracted from the virtual length of the radial head implant (L-RHI), which results in the magnitude of the radial head implant overlengthening in millimeters: (L-RHI) – (L-NRH) = overlengthening. RESULTS: The radiographic measurement technique was validated in a cadaveric study. WHAT TO WATCH FOR: Indications Contraindications Pitfalls & Challenges